Simulasi Pelayanan Terminal Petikemas dalam Bidang Receiving Cargo Berbasis Software Sparkol Videoscribe - Suyanti Suyanti; Cahya Purnomo (Majalah Ilmiah Bahari Jogja, 2019)
This study examines the implementation of learning media development using videoscribe sparkol in order to improve student learning outcomes in Container Management Courses at the Yogyakarta Commercial Shipping Maritime Academy Study Program.This study uses a qualitative and quantitative approach. Data and information collection was carried out using observation, questionnaires and documentation studies. The method used by researchers is Design and Development Research with ADDIE research procedures (Analysis, Design, Development, Implementation, Evaluation). Data was tested using N-Gain analysis.The results of the study concluded that the implementation of learning media development using videoscribe sparkol can improve student learning outcomes. This can be seen from two facts, namely: 1) Based on the results of media expert validation, technical quality assessment obtained results 67.50% in the good category and the media aspect value results 77.88% included in the excellent category. Based on the results of the material expert validation, the results of media aspect assessment is 86.11% and the result of material conformity aspects were 81.25%. Both aspects were included in the excellent category. 2) There is an increase in the average value of interest in learning cadets before and after using videoscribe sparkol media, from 64.67 to 79.67. Based on the results of the N-gain test, an increase in interest in learning cadets gained a gain of 0.43 which is included in the medium category.